Compression molding of Carbon/Polyether ether ketone composites: Squeeze flow behavior of unidirectional and randomly oriented strands. Issue 9 (17th August 2015) - Picher‐Martel, Gilles‐Philippe; Levy, Arthur; Hubert, Pascal
Abstract : Compression molding of randomly oriented strands (ROS) of thermoplastic composite is a new process that enabled the formation of complex shapes with high fiber volume fraction. During compression molding of ROS, several deformation mechanisms occurred. This article focused on the macroscopic squeeze flow mechanism. It ruled how the material will flow and fill intricate features of the mold. The squeeze flow behavior under large strain was investigated for Unidirectional (UD) and ROS. An experimental characterization was performed using an instrumented hot press. Also, to predict the associated thickness reduction, existing models using equivalent viscosity and lubrication assumptions were used. The results showed that large deformation of UD and ROS composite materials is mainly governed by two regimes: a Non‐Newtonian fluid behavior at low strain followed by a yielded phase at large strain. Quantitative indicators were defined to analyze these two phases. They showed that current models available in the literature fail to predict accurately the squeeze flow of thermoplastic composites under high strain (>50%). Also, strands size (especially strand length) has a large effect on the squeeze flow mechanism. This article provided basic process window guidelines in terms of minimum pressure and achievable strain for compression molding of ROS parts. POLYM. COMPOS., 38:1828–1837, 2017. © 2015 Society of Plastics Engineers